Supply Chain Resilience During the Covid-19 Pandemic: Understanding the Role of Collaboration, Visibility, Velocity, and Flexibility in Supply Chain Resilience Using Structural Equation Modeling Approach - Moraga, Melvin V.; Go, Brandon Patrick; Go, Chabeli Eunice; Tan, Hannah; Ledesma, Julia (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Covid-19 has wrought havoc on the supply chain across the world. During the global pandemic, supply chain managers were forced to rely on short-term solutions with little to no impact on their operations. This paper aims to assess the effect of collaboration, visibility, velocity, and flexibility on supply chain resilience. A total of 66 respondents constitutes the sample of the study, consisting of middle management employees across all depots nationwide. Eight research questions and eight hypotheses were generated and tested at 0.05 significance level using descriptive statistics and path analysis to quantify the relationships among multiple variables. Data were then analyzed through partial least squares - structural equation modeling. Results showed that collaboration, visibility, and flexibility have a significant impact on supply chain resilience. However, velocity did not have a significant impact on supply chain resilience. The research concludes that the supply chain capabilities play a crucial role in the supply chain resilience of the company and its supply chain partners. The key recommendations of the paper help enhance these capabilities to improve the resilience of its supply chain.